Stall Sanitation Associated with Cryptosporidium sp. Infection on Calf and Cattle Farmer - Ramadhani, Rafindra; Nurdian, Yudha; Rachmawati, Dwita Aryadina; Utami, Wiwien Sugih; Armiyanti, Yunita; Hermansyah, Bagus; Rahardjo, Angga Mardro (Universitas Airlangga, 2022)
Increasing the cattle population can increase the amount of the waste. Poor management of cage sanitation has the risk of causing a decrease in the health conditions of cattle farmers, such as: diarrhea, nausea, vomiting, and itching, as many as 50% of cattle with diarrhea are infected with Cryptosporidium sp. The highest infection of Cryptosporidium sp. in cattle found in calves. The calf can excrete 1í—1010 oocysts of Cryptosporidium sp. per day. Cryptosporidium sp. also has the potential to cause zoonotic infections that are transmitted from animals to humans. The study aims was to determine the relationship between stall sanitation and Cryptosporidium sp. to calf and cattle farmer. The type of this research was analytic observational with a cross sectional approach conducted in Jatian Village, Pakusari, Jember during October 2021 - March 2022. The primary data was obtained through interviews and observations. The feces of calves and cattle farmer were collected and examined using sedimentation method and modified Ziehl-Neelsen (MZN) staining method. The statistical test used is the chi-square test. The results showed that the prevalence of Cryptosporidium sp. in calves by 14,3% and on cattle farmer by 4,8%. The bivariate analysis showed that that stall location and waste handling were associated with Cryptosporidium for calf (pâ‰¤0.05), and there were no variables that were significantly related to infection in cattle farmers (p>0,05). Cryptosporidium sp. in calves and humans can be caused by several factors, such as environmental factors and hosts. Preventive measures such as maintaining a clean environment including cowshed sanitation and personal hygiene need to be taken to reduce the risk of Cryptosporidium infection from calves to humans, and vice versa.